2017
DOI: 10.7150/ijms.18907
|View full text |Cite
|
Sign up to set email alerts
|

Jak2a regulates erythroid and myeloid hematopoiesis during zebrafish embryogenesis

Abstract: Zebrafish (Danio rerio) are an attractive vertebrate model for the molecular dissection of disease mechanisms. Janus kinase (JAK)/signal transducer and activator of transcription (stat) has been defined through studies of cytokine signaling pathways in mammals. Here, we examined the expression level of Jak2a, which is a homolog of mammalian jak2 in zebrafish, by quantitative reverse transcriptase (RT)-PCR, and the peak of mRNA expression occurred at 3.75 hours post fertilization (hpf). The overexpression of Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Once EPOR binds to EPO, it recruits JAK, a tyrosine kinase that phosphorylates EPOR. In zebra sh, over-expression of JAK/STAT3 signaling pathway promotes erythropoiesis [15][16][17][18] . Here, we found that zebra sh cuedc2 can inhibits human JAK1/STAT3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Once EPOR binds to EPO, it recruits JAK, a tyrosine kinase that phosphorylates EPOR. In zebra sh, over-expression of JAK/STAT3 signaling pathway promotes erythropoiesis [15][16][17][18] . Here, we found that zebra sh cuedc2 can inhibits human JAK1/STAT3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of STAT5 expression modulate the HSC properties, renewal versus differentiation. Recent studies using zebrafish embryos established that JAK2a might have an important role at the level of early hematopoietic progenitor/stem cells before they differentiate into distinct erythroid and myeloid lineages (Zhu et al, 2017). Similar to JAK2 V617F mutants, zebrafish JAK2AV581F mutants also show polycythemia vera phenotype (Ma et al, 2009).…”
Section: Jak/stat Signaling Pathwaymentioning
confidence: 99%
“…Zebrafish has three homologs of JAK: jak1, jak2a, and jak2b [ 76 ]. Overexpression of jak2a in zebrafish embryos increased the expression of gata1 and hemoglobin, indicating a crucial role of jak2a in zebrafish erythropoiesis [ 77 ]. STAT proteins are transcription factors regulated by protein kinases and phosphatases.…”
Section: Using Zebrafish To Study the Regulation Of Erythropoiesismentioning
confidence: 99%